Visual impairment among adult in selected rural area / Dyg Dyg Noor Sandra Ramada Datu Gulam - Datu Gulam, Dyg Dyg Noor Sandra Ramada (Faculty of Health Sciences, 2015)
The research was intended to investigate the self-reported of visual impairment (VI) and its association with demographic data among adult in rural area. Materials and methods: Fourty residents of Kg. Ijok, Selangor aged 40 to 60 years old were recruited in this research. The participants needed to response to the self-reported questionnaire. Then the participant was asked to answer the questionnaires regarding their vision state. The question was "How is your eyesight (with glasses or contacts if you wear them) today?" The response were based on "Excellent", "Good", "Fair", "Poor" (referred to as poor vision) and "Unable to see" (referred to as blindness). Then the visual acuity was measured using Bailey-Lovie LogMAR chart at 6m. Results: The prevalence of male (22.5%) was higher than female (15.0%) in having visual impairment. Those with 60 years old and above (12.5%) were at higher risk to get vision impairment. The prevalence of VI for married participants (32.5%) were increased compared to single/divorced status. People with low education level (25.0%) were seen increased risk to have visual impairment than those with higher education level. Conclusion: Visual acuity testing was a better measurement in determining the VI compared to self-reported method among adults in rural area.